Suvarnadvipa : Ancient Indian Colonies in the Far East. Volume 1: Political History - Majumdar, R.C., (Brill | Manohar Publishers & Distributors, 2024)
South East Asian history is one of the most unique histories, as it was marked by the influences of Indic, Chinese, and local cultures. Suvarnadvipa is a two-volume series, which covers the political and cultural history of South East Asian history. This volume deals with the political history of South Asia during ancient times. It covers the pre-Hindu civilizations in Malaysia and the political conquest of Hindu kingdoms in the prime regions, such as in the Malay Peninsula, Java, Sumatra, Borneo, and Bali, along with the establishment of Hindu civilizations in the Suvarnadvipa region till the seventh century ad. This volume covers the history of Sailendra kingdom comprehensively. The author discusses the political history of Sailendras till the end of the tenth century ad where he also discusses its origins, development, conflict with the Chola rulers and its subsequent decline with the capture and the establishment of Chola influence and the establishment of the Melayu dynasty. This book is essential for scholars and researchers interested in the pre-Islamic history of South East Asia.